Abiotic reactions drive post-wetting soil emissions of N2O and NO and contribute partially to CO2 emissions - Isaac Yagle; Ilya Gelfand (Scientific Reports)
Abstract Pulse emissions of soil trace gases (carbon dioxide: CO2, nitrous oxide: N2O, and nitric oxide: NO) following the wetting of dry soils may contribute disproportionately to total annual trace gas emissions in drylands. These pulses are driven by coupled biotic–abiotic processes that are challenging to partition. Here we measured soil trace gases emissions after the wetting of γ-irradiated and live intact cores of soils with different soil C and N pools, exchangeable cations, and microbial activity. For all soils, the emissions pulse of CO2 and N-oxides was measured within 5 min of wetting. Post-wetting CO2 emission pulses from the live soils were approximately twice as large as those from the γ-irradiated soils and were correlated with soil C content. However, the γ-irradiated soil emitted up to 5 times more N2O and up to 13 times more NO compared with the live soil and emissions were correlated with soil N content. After normalization against the soil inorganic N content, the immediate post-wetting N2O and NO emissions were the same from the live and γ-irradiated soils. The dependence of the post-wetting N2O and NO burst on substrate pools, regardless of the presence of live microbes, suggests an abiotic origin of immediate post-wetting fluxes.